Airway Surface Liquid Osmolality Measured Using Fluorophore-Encapsulated Liposomes - Jayaraman, Sujatha (The Rockefeller University Press, 2001)
The airway surface liquid (ASL) is the thin layer of fluid coating the luminal surface of airway epithelial cells at an air interface. Its composition and osmolality are thought to be important in normal airway physiology and in airway diseases such as asthma and cystic fibrosis. The determinants of ASL osmolality include epithelial cell solute and water transport properties, evaporative water loss, and the composition of secreted fluids. We developed a noninvasive approach to measure ASL osmolality using osmotically sensitive 400-nm-diam liposomes composed of phosphatidylcholine/cholesterol/polyethylene glycol-phosphatidylcholine (1:0.3:0.08 molar ratio). Calcein was encapsulated in the liposomes at self-quenching concentrations (30 mM) as a volume-sensitive marker, together with sulforhodamine 101 (2 mM) as a volume-insensitive reference. Liposome calcein/sulforhodamine 101 fluorescence ratios responded rapidly (<0.2 s) and stably to changes in solution osmolality. ASL osmolality was determined from calcein/sulforhodamine 101 fluorescence ratios after addition of microliter quantities of liposome suspensions to the ASL. In bovine airway epithelial cells cultured on porous supports at an air–liquid interface, ASL thickness (by confocal microscopy) was 22 μm and osmolality was 325 ± 12 mOsm. In anesthetized mice in which a transparent window was created in the trachea, ASL thickness was 55 μm and osmolality was 330 ± 36 mOsm. ASL osmolality was not affected by pharmacological inhibition of CFTR in airway cell cultures or by genetic deletion of CFTR in knockout mice. ASL osmolality could be increased substantially to >400 mOsm by exposure of the epithelium to dry air; the data were modeled mathematically using measured rates of osmosis and evaporative water loss. These results establish a ratio imaging method to map osmolality in biological compartments. ASL fluid is approximately isosmolar under normal physiological conditions, but can become hyperosmolar when exposed to dry air, which may induce cough and airway reactivity in some patients.